+0  
 
0
138
1
avatar

please solve

Guest Apr 26, 2017

Best Answer 

 #1
avatar+4694 
+3

\(-6 = -\frac1{w+5}\)

 

Multiply both sides of the equation by (w + 5) .

-6(w + 5) = -1

 

Divide both sides of the equation by -6 .

w + 5 = 1/6

 

Subtract 5 from both sides of the equation.

w = 1/6 - 5

 

Get a common denominator and combine the fractions.

w = 1/6 - 30/6 = -29/6

hectictar  Apr 26, 2017
Sort: 

1+0 Answers

 #1
avatar+4694 
+3
Best Answer

\(-6 = -\frac1{w+5}\)

 

Multiply both sides of the equation by (w + 5) .

-6(w + 5) = -1

 

Divide both sides of the equation by -6 .

w + 5 = 1/6

 

Subtract 5 from both sides of the equation.

w = 1/6 - 5

 

Get a common denominator and combine the fractions.

w = 1/6 - 30/6 = -29/6

hectictar  Apr 26, 2017

29 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details